SOLUBILITY AND PARTITIONING OF NE, AR, KR AND XE IN MINERALS AND SYNTHETIC BASALTIC MELTS - Broadhurst C.L.; Drake M.J.; Hagee B.E.; Bernatowicz T.J. (My University, 1992)
The solubilities of Ne, Ar, Kr, and Xe gases were measured in natural samples of anorthite, diopside, forsterite, spinel, and synthetic basaltic melts, the samples which represent equilibrium pairs in the Fo-An-Di-SiO2 system. Results show that, in natural minerals, the solubilities of these gases increase with increasing atomic number. In contrast, the solubilities of noble gases in the synthetic basaltic melts decreased with increasing atomic number. The partition coefficients increased with increasing atomic number for all mineral/melt pairs.